2019
DOI: 10.1002/jcb.28583
|View full text |Cite
|
Sign up to set email alerts
|

Antagonistic anticancer effect of paclitaxel and digoxin combination

Abstract: Despite the growing interest in the antitumor effect of cardiotonic steroids, combination treatments with well-established chemotherapy drugs like paclitaxel have been rarely investigated. Moreover, paclitaxel has been suggested as a Na + /K + -ATPase inhibitor. Here we investigated the effect of paclitaxel and digoxin alone or in combination on the viability of human lung (A549) and cervical cancer (HeLa) cell lines and the inhibitory effect of paclitaxel on several mammalian Na + /K + -ATPases. Although the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…Several authors have demonstrated that chemotherapeutic drugs control tumor tissue growth by reducing cell viability[ 28 , 65 , 66 ] and activating distinct signaling transduction pathways that involve PKC[ 67 ], MEK[ 68 ], ERK1/2[ 69 ], Ras[ 70 ], p38MAPK[ 71 ] and NF-κB[ 72 ]. In particular, PX exerts its effects via the activation of different kinase signaling pathways depending on the cell type analyzed[ 73 - 75 ].…”
Section: Discussionmentioning
confidence: 99%
“…Several authors have demonstrated that chemotherapeutic drugs control tumor tissue growth by reducing cell viability[ 28 , 65 , 66 ] and activating distinct signaling transduction pathways that involve PKC[ 67 ], MEK[ 68 ], ERK1/2[ 69 ], Ras[ 70 ], p38MAPK[ 71 ] and NF-κB[ 72 ]. In particular, PX exerts its effects via the activation of different kinase signaling pathways depending on the cell type analyzed[ 73 - 75 ].…”
Section: Discussionmentioning
confidence: 99%
“…Digitoxin also displayed potent cytotoxicity against HeLa cervical cancer cells with an IC50 value of 28 nM after 48 h of exposure [182]. Following a 48 h exposure to digoxin, the viability of both human lung (A549) and cervical cancer (HeLa) cell lines were adversely affected in a concentrationdependent manner, resulting in IC50 values of 31 nM for A549 cells and 151 nM for HeLa cells [183]. The anti-EBV and broad-spectrum anticancer properties, as well as specific anti-cervical cancer activities observed in these cardiac glycosides, make ZINC000095909247 an interesting candidate to probe further.…”
Section: Structural Similarity Search Of the Potential Candidatesmentioning
confidence: 99%
“…Due to its relative simplicity, predictability, precision, and accuracy, assessing particular blood biomarkers of cardiac damage has been proposed as an appealing, legitimate, and new technique to identify and monitor cardiotoxicity in patients treated with chemotherapy [45]. Troponin, B-type natriuretic peptide (BNP), and NT-proBNP are the three main serum markers [46]. The "guardian of the genome" serum P53 shields cells from recurring cancer.…”
Section: Monitoring and Diagnosis Of Cardiotoxicitymentioning
confidence: 99%